NILAI-NILAI LUHUR BUDAYA DALAM PAPADAH BANJAR DI KALIMANTAN SELATAN - Agus Yulianto (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The purpose of this study was to find out the Banjar papadah along with cultural values they have. Banjar papadah can be used to revitalize the noble values of the nation and the relevance of the cultural noble values in Banjar papadah with social life at this time. The research problems are: 1) Banjar papadah along with the cultural values they have where Banjar papadah can be used to revitalize the noble values of the nation; 2) Are the cultural noble values in Banjar papadah still relevant to the life of society today. The study used a qualitative descriptive methodology with library research technique. Based on the analysis, it can be obtained that Banjar papadah-papadah related to human problems as individual, social in the nation and state. They have the cultural noble values that can be used as a reference and guidelines, and those papadah-papadah are still very relevant to the social life and the nation at this time.